2013
DOI: 10.1021/jp405247m
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Oxygen Reduction Activity in Partially Oxidized Tantalum Carbonitrides: Roles of Deposited Carbon for Oxygen-Reduction-Reaction-Site Creation and Surface Electron Conduction

Abstract: Tantalum-oxide-based oxygen-reduction-reaction (ORR) catalysts have the ORR activity only when they are synthesized from tantalum carbonitrides. Namely pure Ta 2 O 5 does not show ORR activity, and carbon or nitrogen in precursors is inevitable to form ORR active sites and to promote ORR. To clarify this reason, we investigated structural and surface electronic properties of tantalum-oxide-based catalysts, which were synthesized by gradually oxidizing tantalum carbonitride under low partial pressure of oxygen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
66
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 28 publications
2
66
0
Order By: Relevance
“…Therefore, the phase transition was probably caused by a change in the valence of titanium. We previously demonstrated that tantalum and zirconium oxide-based catalysts had some oxygen vacancies that acted as active sites for the ORR [6]. In case of the titanium-niobium oxide system, the low valence state of the metal ions does not always indicate the presence of oxygen vacancies.…”
Section: Characterization Of Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the phase transition was probably caused by a change in the valence of titanium. We previously demonstrated that tantalum and zirconium oxide-based catalysts had some oxygen vacancies that acted as active sites for the ORR [6]. In case of the titanium-niobium oxide system, the low valence state of the metal ions does not always indicate the presence of oxygen vacancies.…”
Section: Characterization Of Catalystsmentioning
confidence: 99%
“…Based on the high stability of Group 4 and 5 metal oxide-based compounds in acidic media, low cost, [5,6] and lower solubility in acid solution compared to platinum-based catalysts, these compounds have piqued our interest as they are expected to be stable even under the conditions encountered at the PEFC cathode. Recently, we successfully synthesized oxide-based nanoparticles using oxy-metal phthalocyanines (MeOPc; Me = Ta, Zr, and Ti) as the starting material and multi-walled carbon nanotubes (MWCNTs) as the support as well as the electro-conductive material [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…For both reaction pathways, non-precious metal (NPM) catalysts are desired, considering the cost and scarcity of precious metals. The catalysts obtained by pyrolyzing Fe, N, and C-containing precursors have been widely studied, while oxide-based catalysts also constitute another class of NPM catalysts [4][5][6]. This review article describes an effective approach to obtain a highly active Fe/N/C catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…We previously developed non-platinum cathode electrocatalysts based on group 4 and 5 transition metal oxides that exhibited high stability in acidic media. 1 Among these transition metal oxides, titanium is advantageous because it is a more abundant resource. Our previous studies revealed that titanium oxide-based compounds with multi-walled carbon nanotubes (TiC x N y O z / MWCNTs) prepared by oxidation of a titanium organic complex in low p O2 atmosphere exhibited high ORR activity.…”
Section: Introductionmentioning
confidence: 99%